วิเคราะห์กลยุทธ์สำหรับบริษัทในสมาคมรับสร้างบ้านไทยเพื่อไปดำเนินงานก่อสร้างในสาธารณรัฐแห่งสหภาพเมียนมาร์ สาธารณรัฐประชาธิปไตยประชาชนลาว และราชอาณาจักรกัมพูชา : รายงานผลการวิจัย - วัชระ เพียรสุภาพ (คณะวิศวกรรมศาสตร์ จุฬาลงกรณ์มหาวิทยาลัย, 2017)
Nowadays, housing construction business in Bangkok and metropolitan area is growing gradually with offensive marketing strategies while the business has to face many threats in the close future such as the less of the owners area and the more number of home-builder companies. However, the international construction projects demonstrate high demand of construction in foreign countries. With these reasons, Thai home-builder companies see great opportunity to expand their business in Republic of the Union of Myanmar, Lao People’s Democratic Republic and Kingdom of Cambodia. In the other hand, international construction is much more risk. Furthermore, Thai home-builder companies lack of overseas experience. So, this research aims to analyze strength, weakness, opportunity, threat and analyze strategy for Thai home-builder companies to operate these countries. Factors and strategies are reviewed from previous researches. First, the interview will be made to the experienced for external factors suggestions. Next step, information of external factors will be gathered from public and private sectors, in Thailand and outside sources, for them to understand the international market situation. The information is also revised for adequacy by academic section of Thai home-builder association. After that, the seminar will be held among Thai home-builder companies to present all of the information and evaluate their competency. The data will be used to analyze strategy by brainstorming. Strategies are various by factors of each country. Finally, the strategies will be given opinion by construction companies who have experience in the country and be summarized to the only practical strategies.